2018
DOI: 10.3892/mmr.2018.9782
|View full text |Cite
|
Sign up to set email alerts
|

Systematic screening and identification of novel psoriasis‑specific genes from the transcriptome of psoriasis‑like keratinocytes

Abstract: Psoriasis is a chronic inflammatory skin disease. Keratinocytes (KCs), as skin-specific cells, serve an important role in the immunopathogenesis of psoriasis. In the present study, transcriptome data derived from psoriasis-like KCs were used together with the reported transcriptome data from the skin/epidermis of patient with psoriasis, excluding known psoriasis-associated genes that have been well described in the previous studies according to GeneCards database, to screen for novel psoriasis-associated genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…In this sense, the genes from the transcriptomic profile of cultured cytokine-stimulated keratinocytes overlapping with that of the lesional psoriasis skin only represented up to 5.0% of the psoriatic altered transcriptome [ 68 ]. Wang et al observed similar results regarding the proportion of deregulated genes overlapping between cultured cytokine-stimulated keratinocytes and lesional psoriatic skin while using HaCat keratinocytes, and thus showed once again the limitation of using monolayer systems to obtain a gene alteration profile that mimics the pathology in the most representative manner [ 118 ]. The lack of pathological keratinocytes in studies using these monolayer psoriatic-like models represents a major disadvantage for further transcriptomic studies.…”
Section: Transcriptomic Studies Using In Vitro Modelsmentioning
confidence: 97%
“…In this sense, the genes from the transcriptomic profile of cultured cytokine-stimulated keratinocytes overlapping with that of the lesional psoriasis skin only represented up to 5.0% of the psoriatic altered transcriptome [ 68 ]. Wang et al observed similar results regarding the proportion of deregulated genes overlapping between cultured cytokine-stimulated keratinocytes and lesional psoriatic skin while using HaCat keratinocytes, and thus showed once again the limitation of using monolayer systems to obtain a gene alteration profile that mimics the pathology in the most representative manner [ 118 ]. The lack of pathological keratinocytes in studies using these monolayer psoriatic-like models represents a major disadvantage for further transcriptomic studies.…”
Section: Transcriptomic Studies Using In Vitro Modelsmentioning
confidence: 97%
“…The discovery of an effective novel biologic gives new insights into how beneficial it is to target important immune components, such as cytokines, in alleviating psoriasis exasperation. Hence, it can support other advanced methods, such as the quantification of numerous cytokines receptors using both mRNA and cDNA microarrays [ 43 , 44 ]. Thus, it is crucial to inhibit cytokine signaling if that is the attempted exit strategy for psoriasis.…”
Section: Psoriasis and Cytokines As Biologics Targetmentioning
confidence: 99%
“…TNF-α is a proinflammatory cytokine secreted by DCs, T cells, macrophages and non-immune cells, such as fibroblasts; therefore, its selection in the revolution of inhibitor drugs is promising [ 44 ]. TNF-α acts as the main mediator during the initiation phase of classical psoriasis and can sustain the disease over the long term [ 45 , 46 , 47 ].…”
Section: Main Potential Cytokine Targets In Psoriasismentioning
confidence: 99%
“…Many genomic scanning studies replicated in different populations have demonstrated genetic polymorphisms associated with plaque psoriasis. 13 There are more than 50 chromosomal regions or loci of susceptibility to psoriasis, demonstrating the multigene and epigenetic interaction characteristic of the disease. 14 The genes whose polymorphisms confer susceptibility to plaque psoriasis are related to antigen presentation (ERAP1 and MHC), interferon signaling pathway (IL-28RA and IFIH1), NFkB pathway (ZNF313, REL, TNIP1, TNFAIP3, NFkB1A), 15 of IL-17 (TRAF3IP2), of IL-23 (TYK2, IL-23R, IL-23A, IL-12B) and to the epidermal barrier (LCE3D).…”
Section: Geneticsmentioning
confidence: 99%